Indirect pathological indicators for cardiac sarcoidosis on endomyocardial biopsy - Myung-Jin Cha; Jeong-Wook Seo; Seil Oh; Eun-Ah Park; Sang-Han Lee; Moon Young Kim; Jae-Young Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background The definitive pathologic diagnosis of cardiac sarcoidosis requires observation of a granuloma in the myocardial tissue. It is common, however, to receive a "negative" report for a clinically probable case. We would like to advise pathologists and clinicians on how to interpret "negative" biopsies. Methods Our study samples were 27 endomyocardial biopsies from 25 patients, three cardiac transplantation and an autopsied heart with suspected cardiac sarcoidosis. Pathologic, radiologic, and clinical features were compared. Results The presence of micro-granulomas or increased histiocytic infiltration was always (6/6 or 100%) associated with fatty infiltration and confluent fibrosis, and they showed radiological features of sarcoidosis. Three of five cases (60%) with fatty change and confluent fibrosis were probable for cardiac sarcoidosis on radiology. When either confluent fibrosis or fatty change was present, one-third (3/9) were radiologically probable for cardiac sarcoidosis. We interpreted cases with micro-granuloma as positive for cardiac sarcoidosis (five of 25, 20%). Cases with both confluent fibrosis and fatty change were interpreted as probable for cardiac sarcoidosis (seven of 25, 28%). Another 13 cases, including eight cases with either confluent fibrosis or fatty change, were interpreted as low probability based on endomyocardial biopsy. Conclusions The presence of micro-granuloma could be an evidence for positive diagnosis of cardiac sarcoidosis. Presence of both confluent fibrosis and fatty change is necessary for probable cardiac sarcoidosis in the absence of granuloma. Either of confluent fibrosis or fatty change may be an indirect pathological evidence but they are interpreted as nonspecific findings.